Directed Evolution of Selective Enzymes: Catalysts for Organic Chemistry and Biotechnology. By Manfred T. Reetz. Issue 19 (29th March 2019) - Kries, Hajo
Abstract : Wiley‐VCH, Weinheim, 2016. 308 pp., hardcover, € 139.00.—ISBN 978‐3‐527‐31660‐1